Metal W connected Z-scheme C fibers@WO3-x core-shell composites with highly efficient solar-driven photocatalystic activity. Issue 11 (1st August 2020) - Chen, Yan; Qian, Jingwen; Peng, Zhijian; Fu, Xiuli
Abstract: A series of novel metal W connected Z-scheme C fibers@WO3-x (0 ≤ x < 3) core-shell composites were developed by simply pyrolyzing preoxidized polyacrylonitrile fibers impregnated with slurries of WO3 nanopowder in absolute ethanol in a vacuum furnace. Such structured composites are a kind of more excellent solar-driven photocatalyst for degrading various aqueous organic and inorganic environmental pollutants, compared with pure tungsten oxides catalysts under the same condition. The optimally selected composite catalyst (x = 2.01) was also applied in photocatalytically purifying waste water from paper mills under sunlight, presenting high efficiency in reducing chemical oxygen demand, biology oxygen demand and heavy metal Cr content, displaying great prospect in environmental remediation through removing various toxic industrial chemicals. The greatly enhanced photocatalytic performance could be mainly ascribed to the C fiber core and metal W connection layer between the tungsten oxides and C core in the composites, which can promptly conduct electrons and promote the separation of photogenerated electrons and holes. Moreover, this work provides a simple, eco-friendly and very efficient synthesis approach, which will be of much help to design diversified semiconductors composite structures, and suitable for large-scale production and thus practical industrial application.